2021
DOI: 10.1002/cjoc.202000685
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Fungicidal Activity of Novel Pyrazole‐Containing Strobilurin Derivatives

Abstract: Drug design | Strobilurins | Biological activity | Structure-activity relationships |Cytochrome bc 1 complexIn searching for novel fungicidal leads, a series of pyrazole-containing strobilurins were rationally designed, synthesized and characterized. Bioassay indicated that compound I-7 displayed excellent fungicidal activity against a broad spectrum of plant pathogens such as Gibberella zeae, Rhizoctonia cerealis, Sclerotinia sclerotiorum, Phytophthora infestans, Physalospora piricola and Pellicularia sasakii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…13 7.08 (d, J = 8.9 Hz, 1H), 6.56 (s, 1H), 4.28 (t, J = 5.7 Hz, 2H), 3.82 (q, J = 5.5 Hz, 2H), 2.20 (s, 3H), 2.10 (s, 3H). 13 8.06 (t, J = 5.7 Hz, 1H), 7.25 (d, J = 8.9 Hz, 1H), 7.08 (d, J = 9.0 Hz, 1H), 7.05 (t, J = 53.1 Hz, 1H), 6.56 (s, 1H), 4.31 (t, J = 5.7 Hz, 2H), 3.90 (q, J = 5.7 Hz, 2H), 2.17 (s, 3H). 13 .0 Hz, 1H), 6.56 (s, 1H), 4.28 (t, J = 5.9 Hz, 2H), 3.84 (q, J = 5.7 Hz, 2H), 2.36 (s, 3H), 2.18 (s, 3H).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…13 7.08 (d, J = 8.9 Hz, 1H), 6.56 (s, 1H), 4.28 (t, J = 5.7 Hz, 2H), 3.82 (q, J = 5.5 Hz, 2H), 2.20 (s, 3H), 2.10 (s, 3H). 13 8.06 (t, J = 5.7 Hz, 1H), 7.25 (d, J = 8.9 Hz, 1H), 7.08 (d, J = 9.0 Hz, 1H), 7.05 (t, J = 53.1 Hz, 1H), 6.56 (s, 1H), 4.31 (t, J = 5.7 Hz, 2H), 3.90 (q, J = 5.7 Hz, 2H), 2.17 (s, 3H). 13 .0 Hz, 1H), 6.56 (s, 1H), 4.28 (t, J = 5.9 Hz, 2H), 3.84 (q, J = 5.7 Hz, 2H), 2.36 (s, 3H), 2.18 (s, 3H).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Compound 20 exhibited outstanding in vitro fungicidal activity against Rhizoctonia cerealis , P. infestans , G. zeae , Pellicularia sasakii , Sclerotinia sclerotiorum , and P. piricola with EC 50 values ranging from 0.02 to 0.77 μg/mL, which were much more potent than those of azoxystrobin. A molecular docking study showed that compound 20 could bind with cytochrome bc 1 complex as well as azoxystrobin …”
Section: β-Methoxyacrylate Derivatives As Pesticidesmentioning
confidence: 99%
“…A molecular docking study showed that compound 20 could bind with cytochrome bc 1 complex as well as azoxystrobin. 43 These results demonstrated that the pyrazole ring could act as important side chain in the research and development of novel β-methoxyacrylate fungicides.…”
Section: β-Methoxyacrylate Derivatives As Pesticidesmentioning
confidence: 99%
“…(EC 50 = 53.26 mg/L). In the past few years, BASF had reported several aminoalkylpyrimidine derivates 30–37 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. As shown in the Figure 6 , phenoxypyridine was linked to aminoalkylpyrimidine in various link arms resulting in some molecules with good protective fungicidal activity.…”
Section: Fungicides and Bactericides Containing Phenoxypyridine Scaffoldmentioning
confidence: 99%